Magic tree house : the knight at dawn Vol. 2 - Osborne, Mary Pope.; Murdocca, Sal (New York Random House, 1993)
Eight-year-old Jack and his younger sister Annie use the magic treehouse to travel back to the Middle Ages, where they explore a castle and are helped by a mysterious knight.
"A First stepping stone book."
"RL: 2.2"--Cover p.[4].
Keywords: Time travel -- Fiction; Castles -- Fiction; Middle Ages -- Fiction; Knights and knighthood -- Fiction; Magic -- Fiction; Tree houses -- Fiction